2017
DOI: 10.7556/jaoa.2017.120
|View full text |Cite
|
Sign up to set email alerts
|

First-Time Sports-Related Concussion Recovery: The Role of Sex, Age, and Sport

Abstract: Female athletes aged 11 to 18 years with first-time, sports-related concussions remained symptomatic for a longer period when compared with male athletes of similar age, regardless of sport played. The mechanism behind this difference needs to be further elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…is study also reported that 75% of male athletes showed full recovery from their concussion by 3 weeks compared with 42% of females [13].…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…is study also reported that 75% of male athletes showed full recovery from their concussion by 3 weeks compared with 42% of females [13].…”
Section: Introductionmentioning
confidence: 71%
“…Females were found to be 2 times more likely than males to report severe noise sensitivity following a concussion [12]. Males, on the contrary, show a higher incidence of anterograde amnesia and loss of consciousness than females [13].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Epidemiological studies have demonstrated higher rates of SRC in female university athletes compared to their male counterparts when competing in comparable sports 13,15,17,49 . Relative to males, females also experience more severe symptoms and longer recovery patterns post-SRC 12,48 . Sex differences in cervical spine biomechanics are one hypothesis put forth regarding differences in SRC rates and clinical outcomes post-SRC in males and females 12,14,66 .…”
Section: Introductionmentioning
confidence: 95%
“…4,5 Furthermore, female athletes have a higher concussion symptom burden, longer symptom duration, and worse vestibular ocular deficits. 11,32,46 Despite a higher concussion rate and symptom burden among female athletes, efforts to understand the frequency of head impacts to reduce exposure have rarely included female athletes: a systematic review of head impact kinematic studies revealed that only 1 in 5 included female athletes, 34 and direct male to female comparisons are rare in studies of ice hockey, soccer, and lacrosse. 29,41,52 As a result, we have limited knowledge of head impact exposure differences between genders for similar sports.…”
mentioning
confidence: 99%